Recent structural advances towards understanding of the bacterial type III secretion injectisome. Issue 9 (September 2022) - Jenkins, J.; Worrall, L.J.; Strynadka, N.C.J.
Abstract : The bacterial injectisome is a structurally conserved, syringe-shaped nanomachine that spans the Gram-negative envelope and forms a continuous channel for type III secretion of protein effectors. The injectisome, and the host-modulating effectors it secretes, are essential for the pathogenesis of several Gram-negative bacterial species, and it is a key virulence factor associated with the progression of many clinical and community-based infectious diseases. The molecular structure of the injectisome has been the focus of intense research efforts over the past 30 years, and during this time significant progress has been made in determining the molecular structures of many components. In this review we present major advances in our structural and mechanistic understanding of the injectisome, as facilitated by cryoelectron microscopy approaches. Highlights: The resolution revolution in cryoelectron microscopy has enabled the determination of the molecular structure for many injectisome components, including the core dual membrane-spanning needle complex and key proteins in the cytoplasm. The structural insights generated from these analyses have provided milestone insights as to how the injectisome assembles and functions. Determining the structure of remaining injectisome proteins, including the export gate and translocon pore, will help to develop a more complete understanding of injectisome function on a molecular level. Cryoelectron tomography and subtomogram averaging have enabled a detailed view of the bacterial injectisome in a native cellular context, highlighting key structural differences between species-specific injectisomes and uncovering how the host–pathogen interface is bridged.